(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Pre-clinically, the potential of Eleutherine americana Merr. as antioxidant has been studied, but it’s safety level of its safety has not been widely known. Safety level of ethanolic extract of E. americana Merr leaves (EEEaL) can be detected by acute toxicity test using OECD 425. The aim of this study was to investigate the acute toxicity of EEEaL as the guideline of its safe dose for therapy. This test was performed through OECD 425 (Up and Down Procedure) method with two doses (2000 and 5000 mg/kgbw) of EEEaL administration orally which observed for two weeks toward Wistar rats. The results of the test dose showed no toxic symptoms and they did not cause death in the test animals. Single dosage up to 5000 mg/kgbw also did not show any symptoms of toxicity, and did not cause weight loss until the 14th day of test. The LD50 value of EEEaL is more than 5000 mg/kgbw, suggesting that the plants is practically non toxic according to Loomis classification. Phytochemical screening showed that EEEaL contains compounds such as alkaloids, flavonoids, triterpenoids, steroids, and saponins. Dhaka Univ. J. Pharm. Sci. 18(2): 171-177, 2019 (December)